MENCIPTAKAN SUASANA CERIA DAN SEHAT MELALUI PERMAINAN BALAP KELERENG MENGGUNAKAN SENDOK DI PANTI ASUHAN LKSA JIREH SEMENIFESTARA - Heka Maya Sari Br Sembiring; Boika Firstine Alfarena Simbolon; Talenta Latersia; Enzely Sinambela; Natalia Agnes Lumbantoruan; Maria Cecilia Situmeang (ASOSIASI IDEBAHASA KEPRI, 2026)
Traditional games are a form of play activity that has many benefits for children's physical, social, and emotional development. One traditional game that is easy to play and fun is the marble racing game using spoons. This community service activity aims to create a cheerful and healthy atmosphere for children at the LKSA Jireh Semenifestara Orphanage through the implementation of marble racing games using spoons. The methods used in this activity were observation and documentation, which were carried out during the preparation process, implementation, and after the activity took place. The results of the observations showed that the children were very enthusiastic about participating in the game, appeared more active, cheerful, and enjoyed being with their friends. This game also helped train concentration, balance, patience, and foster sportsmanship and honesty in children. Documentation of the activity strengthened the results of the observations by showing expressions of joy and a more lively atmosphere at the orphanage. Based on these results, it can be concluded that the marble racing game using spoons is effective in creating a cheerful and healthy atmosphere and has a positive impact on the physical and social development of the children at the orphanage.